Integrating Digital Twins and Cyber-Physical Systems for Flexible Energy Management in Manufacturing Facilities: A Conceptual Framework - Rolofs, Gerrit; Wilking, Fabian; Götz, Stefan; Wartzack, Sandro (Electronics, 2024)
This paper presents a conceptual framework aimed at integrating Digital Twins and cyber-physical production systems into the energy management of manufacturing facilities. To address the challenges of rising energy costs and environmental impacts, this framework combines digital modeling and customized energy management for direct manufacturing operations. Through a review of the existing literature, essential components such as physical models, a data platform, an energy optimization platform, and various interfaces are identified. Key requirements are defined in terms of functionality, performance, reliability, safety, and additional factors. The proposed framework includes the physical system, data platform, energy management system, and interfaces for both operators and external parties. The goal of this framework is to set the basis for allowing manufacturers to reduce energy consumption and costs during the lifecycle of assets more effectively, thereby improving energy efficiency in smart manufacturing. The study highlights opportunities for further research, such as real-world applications and sophisticated optimization methods. The advancement of Digital Twin technologies holds significant potential for creating more sustainable factorie
Keywords: Digital Twin; energy system; model-based systems engineering; simulation; CPPS; energy management; EMS